واقع إدارة التغيير في مؤسسات التعليم العالي ومتطلبات تطبيقها كما يتصورها أعضاء الهيئة التعليمية فيها (دراسة ميدانية على جامعة دمشق ) - الحسنية سليم; الجزائرلي معاذ الشرفاوي; منصور هديل (Latakia University Journal - Economic and Legal Sciences Series, 2016)
هدف البحث إلى التعرف على واقع إدارة التغيير في مؤسسات التعليم العالي ومتطلبات تطبيقها كما يتصورها أعضاء الهيئة التعليمية فيها. والتعرف على الفروقات بين درجات إجابات أفراد عينة البحث على استبيان واقع إدارة التغيير تبعاً لمتغيرات البحث: (الجنس، الرتبة الأكاديمية، سنوات الخبرة). واعتمدت الباحثة على المنهج التحليلي الوصفي، واستخدمت استبيانا مكونا من خمسة مجالات: (الرؤية المستقبلية لمؤسسات التعليم العالي، الثقافة التنظيمية الداعمة للتغيير، نظرة العاملين لعملية التغيير، استراتيجية المؤسسات التعليمية في عملية التغيير، المتطلبات المالية والفنية). وتكونت عينة البحث من (231) عضو هيئة تعليمية في جامعة دمشق. ومن أهم النتائج التي توصل إليها البحث: 1) لا توجد فروق ذات دلالة إحصائية عند مستوى الدلالة (0.05) بين متوسطات درجات إجابات أفراد عينة البحث على استبيان واقع إدارة التغيير ومتطلباتها وفق متغير الجنس. 2) وجود فروق بين درجات إجابات المدرسين على استبيان واقع إدارة التغيير ومتطلباتها تُعزى إلى متغير الرتبة الأكاديمية لصالح أعضاء الهيئة التعليمية . 3) وجود فروق بين درجات إجابات المدرسين على استبيان واقع إدارة التغيير ومتطلباتها تُعزى إلى متغير عدد سنوات الخبرة لصالح أعضاء الهيئة التعليمية الذين لديهم سنوات خبرة ما بين (11- 20) سنة. وفي ضوء النتائج التِي توصل إليها البحث تقترح الباحثة ما يلي: ضرورة قيام الإدارات العليا في وزارة التعليم بفتح المجال أمام الأساتذه على اختلاف مستوياتهم الإدارية للمشاركة في عملية صناعة القرارات. ضرورة تعزيز ثقة الموظفين بنظام التقويم، وذلك من خلال قيام الإدارة بالعمل على أن تكون تقديرات تقويم الأداء علنية، وليست سرية. خلق ثقافة ومناخ تنظيمي يشجع الاكايدميين وذوي الخبرات في مؤسسات التعليم العالي على التوجه نحو التميز والإبداع والابتكار. The research aims to identify the reality of change management in educational institutions and the requirements of their application as perceived by members of its teaching. And to identify the differences between the degrees of sample member’s responses to a questionnaire of reality of change management depending on the research variables (sex, academic rank, years of experience). The researcher relied on the analytical descriptive method, and used a questionnaire consisting of five areas:(future vision of educational institutions, organizational culture that support change, workers look to the process of change, a strategy of educational institutions in the process of change, financial and technical requirements). The sample consisted of (231) member of the faculity staff in Damascus University. Among the most important findings of the research: 1) There is no statistically significant differences in the significance level (0.05) between the mean of sample member’s responses to a questionnaire of the reality of change management and its requirements in accordance to the sex variable. 2) There are differences between the degrees of teachers responses to a questionnaire of the reality of change management and its requirements in accordance to the variable of academic rank according to the faculty staff members. 3) There are differences between the degrees of teachers responses to a questionnaire of the reality of change management and its requirements in accordance to the variable of number of years of experience according to the teaching staff members who have years of experience between (11-20) years. In light of the research findings , the researcher suggests the following: The necessity of opening the door to professors at different administrative levels to participate in the decision-making process by the Ministry of Education. Ø The necessity of strengthen the staff confidence of the evaluation system through the administration work to be the performance estimates more public , not secret. Ø Create an organizational culture and climate encourage the academics and expertise people higher education institutions to move towards excellence, creativity and innovation.